Biofilm Producing Staphylococcus epidermidis (RP62A Strain) Inhibits Osseous Integration Without Osteolysis and Histopathology in a Murine Septic Implant Model. Issue 4 (19th November 2019) - Tomizawa, Takuya; Ishikawa, Masahiro; Bello‐Irizarry, Sheila N.; de Mesy Bentley, Karen L.; Ito, Hiromu; Kates, Stephen L.; Daiss, John L.; Beck, Christopher; Matsuda, Shuichi; Schwarz, Edward M.; Nishitani, Kohei
ABSTRACT: Despite its presence in orthopaedic infections, Staphylococcus epidermidis 's ability to directly induce inflammation and bone destruction is unknown. Thus, we compared a clinical strain of methicillin‐resistant biofilm‐producing S. epidermidis (RP62A) to a highly virulent and osteolytic strain of methicillin‐resistant Staphylococcus aureus (USA300) in an established murine implant‐associated osteomyelitis model. Bacterial burden was assessed by colony forming units (CFUs), tissue damage was assessed by histology and micro‐computed tomography, biofilm was assessed by scanning electron microscopy (SEM), host gene expression was assessed by quantitative polymerase chain reaction, and osseous integration was assessed via biomechanical push‐out test. While CFUs were recovered from RP62A‐contaminated implants and surrounding tissues after 14 days, the bacterial burden was significantly less than USA300‐infected tibiae ( p  < 0.001). In addition, RP62A failed to produce any of the gross pathologies induced by USA300 (osteolysis, reactive bone formation, Staphylococcus abscess communities, marrow necrosis, and biofilm). However, fibrous tissue was present at the implant‐host interface, and rigorous SEM confirmed the rare presence of cocci on RP62A‐contaminated implants. Gene expression studies revealed that IL‐1β, IL‐6, RANKL, and TLR‐2 mRNA levels in RP62A‐infected bone were increased versus Sterile controls. Ex vivo push‐out testing showed that RP62A‐infected implants required significantly less force compared with the Sterile group (7.5 ± 3.4 vs. 17.3 ± 4.1 N; p  < 0.001), but required 10‐fold greater force than USA300‐infected implants (0.7 ± 0.3 N; p  < 0.001). Taken together, these findings demonstrate that S. epidermidis is a commensal pathogen whose mechanisms to inhibit osseous integration are limited to minimal biofilm formation on the implant, and low‐grade inflammation. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:852‐860, 2020